Localizing Energy Sources and Sinks in Plates Using Power Flow Maps Computed From Laser Vibrometer Measurements. (1998) - Arruda, J.R.F.; Mas, P.
Abstract : This paper presents an experimental method especially adapted for the computation of structural power flow using spatially dense vibration data measured with scanning laser Doppler vibrometers. In the proposed method, the operational deflection shapes measured over the surface of the structure are curve-fitted using a two-dimensional discrete Fourier series approximation that minimizes the effects of spatial leakage. From the wavenumber-frequency domain data thus obtained, the spatial derivatives that are necessary to determine the structural power flow are easily computed. Divergence plots are then obtained from the computed intensity fields. An example consisting of a rectangular aluminum plate supported by rubber mounts and excited by a point force is used to appraise the proposed method. The proposed method is compared with more traditional finite difference methods. The proposed method was the only to allow the localization of the energy source and sinks from the experimental divergence plots.